The Practice of Repentance in Medieval Iceland: Indigenous Ideas and Christian Influences - Kanerva Kirsi (Finland, 2022)
This article deals with repentance as emotion in medieval Icelandic culture circa 1200–1400. It studies representations of repentance in medieval saga literature, concentrating on repentance as practice (as defined by Monique Scheer), including attitudes towards and meanings given to repentance in religious and secular contexts.
Iceland was Christianized in 999/1000, but conversion did not result in radically drastic changes of mentality or worldview. Confrontation of two worldviews, Christian and indigenous, occurred when Christian ideas of penitence were adopted. In Christian thought, repentance as emotion was associated with certain norms and emotional practice. Sometimes these “foreign” norms and expectations in terms of strong displays could collide with vernacular theories of emotion: some emotions considered good and appropriate in Christian thought might be viewed from the native perspective as bad, unwanted, or detrimental to health.
The sources used in this study consist of vernacular sagas written in Iceland circa 1200–1400. I will concentrate on two cases, one in Dámusta saga and one in Laxdæla saga. I will examine the representation of repentance in the two sources intertextually in connection with other medieval Icelandic sagas in order to show how Dámusti’s and Guðrún’s repentance as emotional practice would have been viewed in light of vernacular conceptions of emotions. I will suggest that while there existed a model for repentance that emphasized the bodily nature of the experience and drastic emotional expression, this was not the only model. Another type, which represented the practice of repentance as a ritualistic performance, avoided excessive emotions and bodily displays of remorse. The first model was problematic because it ran counter to the indigenous conceptions of what emotions are and how they operate, and thereby contested the local norms of emotional expression.